Hubungan Harga Diri dan Prasangka Gender Dengan Kecenderungan Perilaku Cyberbullying Pelajar Jakarta - Teguh Lesmana (Jurnal Psikologi TALENTA, 2019)
The phenomenon of cyberbullying often occurs in Indonesia, especially in adolescents. The case of cyberbullying tends to occur because of the problem of self-esteem in the perpetrators of cyberbullying. Apart from self-esteem issues, it was also found that men tend to do cyberbullying more often than women. The purpose of this study was to determine the relationship of self-esteem and gender prejudice to cyberbullying behavior on students in Jakarta. The research method used is the stratified random sampling technique. This research was conducted to high school and vocational high school students on an equal level in DKI Jakarta with a sample of 435 people. The results of this study indicate that there is a significant relationship between self-esteem and the tendency of cyberbullying behavior. In addition, gender prejudice was also found to have a significant relationship with the tendency of cyberbullying behavior. These results are expected to be the basis for educators and parents and the government to provide early education to adolescents about the importance of developing tolerance and respect for the opposite sex and providing education on how to use social media wisely.